The Coverage of the Issue on “The Full Knights of Glory Order of Other Nationalities Born or Having Lived and Worked in Armenia before the War” in Armenian HistoriographyThe Coverage of the Issue on “The Full Knights of Glory Order of Other Nationalities Born or Having Lived and Worked in Armenia before the War” in Armenian Historiography - Gasparyan, Volodya (History and Culture, 2022)
Armenian people has had an active participation in the Second World War and in the Great Patriotic War and had its great contribution to the Victory against Fascism - the enemy of humanity.More than 600 000 Armenians participated in the War, 200 000 of them passed away in the front line. 106 Armenian soldiers were awarded with the highest title of the Hero of the Soviet Union (it should be mentioned, that Azerbaijan had 43 heroes, which were mainly Kurds, Talyshs, Tatars). 26 Armenian soldiers were awarded with three degrees of Glory Order and became full knights of the Glory Order, the status of which was equal to the status of the Hero of the Soviet Union.10 soldiers of other nationalities were also awarded with the title of the Hero of the Soviet Union, who were born or had lived and worked in Armenia before the War (5 Russians, 1 Ukrainian, Greek, Assyrian, Kurdish and Azerbaijani).Since, different statistics on the number of the Full Knights of Glory Order have been mentioned up till now we tried to find out about it in our article. That will definitely support the tutors at schools, military institutions, and higher education institutions in their daily work and according to us, will contribute to the important task of military-patriotic upbringing of the younger generation.
Keywords: war; army; historiography; Armenia; saboteur; hero of Soviet Union; Glory Order knight